Economic Burdens of PFAS in Residual Streams from Drinking Water Treatment - Alhitta, Amna H M (My University, 2026)
Per- and polyfluoroalkyl substances (PFAS) are highly persistent environmental pollutants linked to adverse health effects, with drinking water serving as a primary human exposure route. While previous studies often focus on treatment efficiency and operational costs of PFAS removal, the economic burdens of PFAS transferred to residual streams generated within drinking water treatment processes remain understudied. This study develops a conceptual framework to investigate the fate of PFAS compounds transferred into residual streams and to assess the associated economic impacts. Considering both local recirculation into raw water systems and release into surrounding aquatic environments, the framework was applied to three Swedish drinking water treatment plants with distinct hydrological conditions. The results demonstrate that hydrological conditions heavily dictate PFAS transport pathways. Closed hydrological systems exhibit high recycling rates and dominant local recirculation costs. In contrast, open systems show limited recirculation but significant downstream transport, resulting in substantial environmental burden costs. Sensitivity analysis revealed that water residence time and time horizon significantly impact these patterns, while higher recipient removal efficiency reduces environmental costs. Conversely, increasing the number of recipient GAC filter units elevates environmental costs. Furthermore, even small annual PFAS masses can generate substantial downstream treatment burdens due to the high cost of removing diluted pollution. Ultimately, the study highlights the necessity of source-oriented management strategies, showing that minimizing PFAS transfer to residual streams is critical to reducing future environmental disadvantages and costly downstream treatment.
Keywords: PFAS, economic burdens, residual streams, drinking water treatment, hydrological pathways, recirculation, release, local recirculation cost, downstream, environmental burden cost